The Promotion of Hate Speech: From a Media and Journalism Perspective - Said-Hung, Elias Manuel; Montero-Díaz, Julio; Sánchez-Esparza, Marta (Journalism Practice, 2024)
This work presents the key ideas of the 13 works that make up the special issue, “The Role of News Media in Promoting Hate Speech,” exploring the mechanisms by which hate speech spreads in media-related environments. The objective of this collection of studies is. The authors of these works, hailing from Spain, the United States, India, Portugal, and Norway, have contributed to establishing an approach to the central issue from diverse perspectives, including a legal perspective and addressing elements associated with journalistic practice and the dissemination of hate speech in current digital communication scenarios and help to exacerbate the polarization and prejudice in the public opinion of our current societies.
Keywords: hate speech; social media; journalist; digital media; mass media; professional practice; social conflicts‌; Scopus